(untitled) (Acta Polytechnica CTU Proceedings, 2022)
The LVR-15 research reactor is operated with a tube type fuel IRT-4M. Due to fuel’s unique concentric square annular shape with, coolant flow is subject to significant pressure driven crossflow. Detailed calculation of such flow patterns is beyond capabilities of standard system codes used for the thermal hydraulic safety analysis. To assess safety of core designs consisting of the IRT-4M fuel assemblies, a new subchannel code is under development at Research Centre Rež and Czech Technical University in Prague. Computer program SUBSALS is single phase, steady state, subchannel solver in development. Rigid computational mesh describes IRT-like geometries, and it is also suitable for other specific doubly connected ducts. In this contribution, general description of calculation procedure and computational capabilities is presented along with code-to-code comparison. It could be used as proof of concept for future improvements in thermal hydraulic calculations of research reactors.